Usefulness of the amniotic membrane in the scaring process - Marjoris Piñera Martínez; Odenys Rodríguez Santiesteban; Sergio Del Valle Piñera (Centro Provincial de Información de Ciencias Médicas, 2020)
The case reports of two patients admitted to Saturnino Lora Teaching Clinical Surgical Provincial Hospital in Santiago de Cuba are described: an old man that received a coronary revascularization in the Cardiovascular Surgery Service and presented infection of the surgical site, as well as suture material rejection; and a young adult woman assisted in the Intensive Cares Unit due to a bacterial endocarditis, who after two months of hospitalization developed a grade III pressure ulcer in the sacral region, with a diameter of 8 cm and bony exposure. In these patients all the established therapeutic protocols had been implemented according to the type of disorder, but if there is no healing of the lesions, it was decided to apply amniotic membrane dressings, with which there was a favorable clinical course and the scaring of the wounds was achieved.